2013
DOI: 10.1115/1.4007835
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Loss Sources in a Fan Operating With Continuous Inlet Stagnation Pressure Distortion

Abstract: The viability of boundary layer ingesting (BLI) engines for future aircraft propulsion is dependent on the ability to design robust, efficient engine fan systems for operation with continuously distorted inlet flow. A key step in this process is to develop an understanding of the specific mechanisms by which an inlet distortion affects the performance of a fan stage. In this paper, detailed full-annulus experimental measurements of the flow field within a low-speed fan stage operating with a continuous 60 deg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…As a result, the total pressure loss at the outlet plane increased by up to 7% relative to the clean case. Similar conclusions were reached by Gunn et al [20], who measured a 4.6% reduction in fan efficiency due to a 60° sector of total pressure loss. The measurements revealed that the loss in efficiency is due to the fact that the rotor operates at an off-design condition around the entire annulus.…”
supporting
confidence: 88%
“…As a result, the total pressure loss at the outlet plane increased by up to 7% relative to the clean case. Similar conclusions were reached by Gunn et al [20], who measured a 4.6% reduction in fan efficiency due to a 60° sector of total pressure loss. The measurements revealed that the loss in efficiency is due to the fact that the rotor operates at an off-design condition around the entire annulus.…”
supporting
confidence: 88%
“…• Co-rotating swirl at the entry of the distortion • Counter-rotating swirl at the exit of the distortion • Alteration and change of shape of the distortion on its way downstream through the compressor • Variation of incidence and blade loading • Mass flow redistribution They were also described by Gunn et al [24], who analysed another fan geometry operating with a continuous inlet stagnation pressure distortion, although their distortion was generated in a different way by a 60 • sector gauze.…”
Section: The Distortion In Generalmentioning
confidence: 94%
“…Another study done by Govardhan and Viswanath [12] reports the combined effect of inlet flow distortion and swirl on an axial fan stage and it was found that swirl causes deterioration in performance in addition to that caused by distortion. Gunn et al [13] have conducted experiments on a low speed, low aspect ratio axial fan stage operating under 60° sector inlet total pressure distortion to understand fluid mechanics governing the upstream distortion interaction and distortion transfer through stage. They found substantial flow separation near the tip region in rotor and near the hub region of stator under the influence of distortion and thereby causes reduction in performance of stage.…”
Section: Introductionmentioning
confidence: 99%